Microsoft Word Skills Development Training for Final Semester Students: Pelatihan Pengembangan Keahlian Microsoft Word Bagi Mahasiswa Semester Akhir - Wardhani, Anindya Khrisna; Nur Latifah Dwi Mutiara Sari; Astrid Novita Putri (Institut Teknologi dan Bisnis Semarang, 2024)
The use of Microsoft Word skills is important in the academic world, especially for final semester students who are completing their final assignments. This community service aims to provide Microsoft Word skill development training for final semester students with a focus on increasing the efficiency and quality of preparing thesis reports. Through a series of intensive training sessions, students will be equipped with an in-depth understanding of Microsoft Word's advanced features that can support the research process and preparation of scientific documents. This training was attended by 129 participants from various universities via zoom meetings. The activity lasted for 4 hours consisting of material presentation, case studies, questions and answers and ended with closing. After participating in this activity, participants receive significant benefits in improving students' abilities so that they can make maximum use of word processing software, and can produce quality final assignment reports that meet academic standards. Apart from that, community service this time can also motivate students to develop information technology skills which will be an added value in their future careers.